The Effect of Using Digital Geography Textbooks Based on the Merdeka Curriculum on Students’ Learning Motivation and Critical Thinking Skills - Ardiati Ardiati; Rahmi Novalita; Cut Khairani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aimed to analyze the effect of using a digital geography textbook on students’ learning motivation and critical thinking skills in Grade X at SMA Negeri 1 Tangse. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 32 students selected through purposive sampling. Data were collected through questionnaires and documentation and analyzed using a paired-sample t-test at a significance level of 0.05. The results showed a significant difference between students' pretest and posttest scores in learning motivation after the implementation of the digital geography textbook (t = 28.651; p = 0.000 0.05). The mean learning motivation score increased from 56.41 to 68.95. In addition, there was a significant difference between the pretest and posttest scores of students' critical thinking skills (t = 49.193; p = 0.000 0.05), with the mean score increasing from 61.41 to 70.22. These findings indicate that the use of a digital geography textbook positively affects students' motivation to learn and critical thinking skills. A systematically designed, digitally based geography textbook can enhance students' engagement in the learning process and foster the development of critical thinking skills in Geography.